Analysis of short-range order in Cu3Au using X-ray pair distribution functions. (15th February 2017) - Owen, L.R.; Playford, H.Y.; Stone, H.J.; Tucker, M.G.
Abstract: Cu3 Au is often cited as a case example of a metallic system exhibiting both short-range order in the solid solution phase and a long-range order-disorder transition. In this work, X-ray total scattering data obtained from the in situ heating of a gas-atomised powder sample of Cu3 Au are used to demonstrate the suitability of total scattering, in conjunction with large-box modelling, for the analysis of short-range order in alloys. The existence of an ordering transition at c. 400° is confirmed, and the development of short-range order reminiscent of the L12 long-range ordered structure is observed prior to this transition. Furthermore, it is found that a degree of short-range order is present even in quenched samples (usually assumed to be completely random) which throws into question the identification of short-range order in previous ex situ studies. It is demonstrated that total scattering can be used successfully to identify the type and degree of ordering, differences in the bond length distributions in the first coordination shell and to suggest a likely mechanism for the formation of order in the system. Graphical abstract: Image 1